Exciton–Exciton Interactions in Coaxial Double Quantum Rings - Vanik Shahnazaryan; Vram Mughnetsyan; Ivan Shelykh; Hayk Sarkisyan (Nanomaterials, 2019)
We study theoretically the quantum states of two interacting excitons in coaxial double quantum rings. An interplay between exciton−exciton Coulomb interactions and specific geometry of the structure leads to the emergence of peculiar energy spectrum of two exciton system. We develop a semi-analytic approach providing highly accurate energies of system in the wide range of values of geometrical parameters relevant to experimental realizations.